Riwayat pemberian ASI eksklusif dan MPASI dini sebagai prediktor terjadinya stunting pada baduta di Kabupaten Timor Tengah Selatan, Nusa Tenggara Timur - Asweros Umbu Zogara; Hamam Hadi; Tony Arjuna (Alma Ata University Press, 2014)
ABSTRACTBackground: Stunting is a chronic nutrition problem that reflects failure in growth accumulated before and after birth. Many factors affect the incidence of stunting, among others are exclusive breastfeeding and early introduction of complementary food. The result of a survey carried out by FAO, WFP, and UNICEF in 2010 showed the prevalence of stunting in children under five years old at Timor Tengah Selatan District was 61%.Objectives: To find out whether history of exclusive breastfeeding and early introduction of complementary food were predictors of stunting in children under two years old at Timor Tengah Selatan District.Methods: This was observational study by cross sectional design used quantitative and qualitative methods. Qualitative data obtained from focus group discussion. Subject of the study consisted of 408 children 6 to 24 months from 14 villages at Amanuban Barat and Kie Subdistrict selected through simple random sampling technique. Retrieval of data used a structured questionnaire. Stunting in children under two years old measured by indicators of body length by age. Data were analysed by chi square and logistic regression tests with 95% confident interval.Results: The proportion of stunting in children under two years old at Amanuban Barat and Kie Subdistrict was 49%. The proportion of exclusive breastfeeding was 61%, and early introduction of complementary food was 36,8%. Exclusive breastfeeding and early introduction of complementary food were not factors affecting the incidence of stunting in children under two years old. Factors more strongly affecting the incidence of stunting in children under two years old were energy intake and characteristics of parents that comprised education and occupation.Conclusions: Exclusive breastfeeding and early introduction of complementary food were not predictors of stunting in children under two years old at Amanuban Barat and Kie Subdistrict.KEYWORDS: stunting, exlusive breastfeeding, early introduction of complementary food, children under two years oldABSTRAKLatar belakang: Stunting merupakan masalah gizi kronis yang dapat memberikan gambaran kegagalan pertumbuhan yang terakumulasi sejak sebelum dan sesudah kelahiran. Faktor-faktor yang turut mempengaruhi kejadian stunting diantaranya pemberian ASI eksklusif dan pengenalan MPASI dini. Hasil survei yang dilakukan FAO, WFP, dan UNICEF tahun 2010 menunjukkan prevalensi stunting pada balita di Kabupaten Timor Tengah Selatan mencapai 61%.Tujuan: Untuk mengetahui apakah riwayat pemberian ASI eksklusif dan MPASI dini merupakan prediktor terjadinya stunting pada anak di bawah dua tahun (baduta) di Kabupaten Timor Tengah Selatan.Metode: Penelitian ini merupakan penelitian observasional dengan rancangan cross-sectional yang menggunakan metode kuantitatif dan kualitatif. Data kualitatif yang diperoleh melalui focus group discussion. Sampel penelitian sebanyak 408 anak berusia 6-24 bulan yang berasal dari 14 desa di Kecamatan Amanuban Barat dan Kie yang dipilih menggunakan teknik simple random sampling. Pengambilan data menggunakan kuesioner terstruktur. Stunting pada baduta diukur menggunakan indikator panjang badan menurut umur (WHO 2005). Analisis data menggunakan uji chi square dan regresi logistik dengan 95% confident interval.Hasil: Proporsi baduta yang mengalami stunting sebesar 49%. Proporsi pemberian ASI eksklusif pada baduta sebesar 61% dan proporsi pemberian MPASI dini sebesar 36,8%. Pemberian ASI eksklusif dan MPASI dini bukan merupakan faktor yang mempengaruhi terjadinya stunting pada baduta. Faktor-faktor yang lebih kuat pengaruhnya terhadap terjadinya stunting pada baduta adalah asupan energi dan karakteristik orang tua yang meliputi pendidikan dan pekerjaan orang tua.Kesimpulan: Pemberian ASI eksklusif dan MPASI dini bukan merupakan prediktor terjadinya stunting pada baduta di Kecamatan Amanuban Barat dan Kie.KATA KUNCI: stunting, ASI eksklusif, MPASI dini, baduta